Pandangan Ulama dan Tokoh Adat terhadap Tradisi Praktik Upah Mengupah dalam Proses Penyelenggaraan Jenazah di Nagari Jambak Selatan Kec. Luhak Nan Duo Kab. Pasaman Barat - Febrianto, Muhammad; Firdaus, Beni (Lembaga Yasin AlSys, 2026)
The tradition of wage-based practices in the process of funeral management remains a socio-religious phenomenon that continues to exist and develop among the community of Nagari Jambak Selatan, Luhak Nan Duo Subdistrict, West Pasaman Regency. This practice has generated debate because funeral management in Islam is a fardhu kifayah obligation that should ideally be carried out voluntarily without commercial motives. This study aims to analyze wage-based practices in funeral management and to examine the views of ulama and customary leaders regarding this practice. This study employed a qualitative method with a field research design. Data were collected through observation, in-depth interviews with ulama, customary leaders, and community members, as well as documentation, and were then analyzed descriptively-analytically. The results showed that wage-based practices in funeral management in Nagari Jambak Selatan were not mandatory and were not determined based on a specific tariff, but were given voluntarily as a form of appreciation and gratitude. Ulama and customary leaders generally viewed this practice as permissible in Islam as long as it was carried out sincerely, was not imposed, and did not turn funeral management into a field of commercialization. Thus, the tradition of wage-based practices in funeral management can be accepted both shar‘i and customarily as long as it continues to uphold the values of sincerity, mutual cooperation, and mutual assistance. The implications of this study indicate that public understanding of this practice needs to be continuously strengthened so that it does not burden bereaved families and remains aligned with the principles of Islamic teachings and local wisdom.